Stroke Survivors’ Experiences of Sleep: A Hermeneutic Phenomenological Study - Ida Kathrine Westh; Louise Abildgaard Moeller; Marit Otto; Pia Dreyer; Grethe Andersen; Janne Kaergaard Mortensen (Nursing Research and Practice)
Conclusions: The participants experienced frequent and substantial changes in sleep which affected their everyday lives in various ways.